Do organisational commitments matter in teaching approaches among academics in elite universities in Beijing?. Issue 7 (9th August 2017) - Zhang, Li-fang; Evans, Carol; Postiglione, Gerard A.
Abstract: This research investigated the statistical predictive power of organisational commitments for academics' teaching approaches. Participants were 268 academics working in six elite universities in Beijing, mainland China. Results showed that academics' organisational commitments as measured by the Organisational Commitment Inventory significantly predicted their teaching approaches as assessed by the Approaches to Teaching Inventory – beyond gender, age, taught academic discipline, academic rank and type of institution. Limitations and theoretical contributions of the study are noted; and practical implications of the findings are discussed in relation to academics and university senior managers.